2019
DOI: 10.3390/pr7110820
|View full text |Cite
|
Sign up to set email alerts
|

Thermophysical Properties and CO2 Absorption of Ammonium-Based Protic Ionic Liquids Containing Acetate and Butyrate Anions

Abstract: Ionic liquids, which are classified as new solvents, have been identified to be potential solvents in the application of CO2 capture. In this work, six ammonium-based protic ionic liquids, containing ethanolammonium [EtOHA], tributylammonium [TBA], bis(2-ethylhexyl)ammonium [BEHA] cations, and acetate [AC] and butyrate [BA] anions, were synthesized and characterized. The thermophysical properties of the ammonium-based protic ionic liquids were measured. Density, , and dynamic viscosity, , were determined at te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 44 publications
3
23
0
Order By: Relevance
“…As temperature increases, the volume of ionic liquids increases, and the density of the ionic liquids decreases accordingly. At higher temperatures, the intermolecular forces between the constituent ions weaken, and this increases the mobility of the ions which in turn increases the volume of these ions [ 37 , 52 , 53 ]. Further analysis also revealed that [EHA][C5] has the highest density values compared to the rest of the ammonium-based PILs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As temperature increases, the volume of ionic liquids increases, and the density of the ionic liquids decreases accordingly. At higher temperatures, the intermolecular forces between the constituent ions weaken, and this increases the mobility of the ions which in turn increases the volume of these ions [ 37 , 52 , 53 ]. Further analysis also revealed that [EHA][C5] has the highest density values compared to the rest of the ammonium-based PILs.…”
Section: Resultsmentioning
confidence: 99%
“…Further analysis also revealed that [EHA][C5] has the highest density values compared to the rest of the ammonium-based PILs. The small size of [EHA] cation compared to [BEHA] cation affects local packing of the PIL structure and thus contributes to the increase in the density values of [EHA][C5] [ 37 , 54 ]. Comparable observations using PIL with ethylammonium cation were also found by several researchers, in which an increasing trending packing efficiency was proportional with the decreasing of molecular weight [ 51 , 55 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ethanolammonium butyrate 1.073 [17] 1.177 9.71% Bis(2-ethylhexyl) ammonium butyrate 0.870 [17] 0.935 7.48% 1.001 15.13% Tributylammonium acetate 0.912 [17] 0.928 1.71% 1.065 16.77%…”
Section: Specific Mass (G/cm³)mentioning
confidence: 99%